Keragaan dan Analisis Rasio Keuangan Usaha Penjualan Kedelai (Studi Kasus pada PT. Sari Eco di Desa Gudang Kecamatan Tanjungsari Kabupaten Sumedang Jawa Barat) - Ana Yohana; Mochammad Ramadhan Mahendra (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to determine the performance of soybean sales at PT. Sari Eco and know the company's financial performance seen from the liquidity ratio, solvency ratio, profitability ratio and activity ratio. This research uses a case study method through a quantitative descriptive approach. The result of this research is PT. Sari Eco is a company engaged in the supply of food ingredients that has sold a lot of soybeans to various tofu and tempeh craftsmen in Sumedang Regency. The company was founded in 2000 with the founder Mr. Ace as owner. With the support of the potential of soybeans which are often used in making processed tofu and tempeh in Sumedang Regency, PT. Sari Eco has won a lot of trust from tofu companies and is always ready to partner with other companies. Based on the results of research for financial performance assessment using financial ratio analysis, namely the analysis of liquidity ratios, solvency ratios, profitability ratios and activity ratios at the company PT. Sari Eco. The company's financial performance of PT. Sari Eco is not healthy which is decreasing every month. The company is having difficulty selling its products due to the Covid-19 pandemic and the rising soybean prices. This must be considered so that the users of the company's assets experience improvements every month.